Numerical Investigation of Dual Metal Hydride Bed Based Thermochemical Energy Storage System - Sumeet Kumar Dubey; K. Ravi Kumar; Vinay Tiwari; Umish Srivastva (SolarPACES Conference Proceedings)
Thermochemical energy storage system is known for good thermal stability and high energy storage density. Metal hydride based thermochemical energy storage systems are reported to store thermal energy at higher temperatures. In this analysis, NaMgH2F and Mg2NiH4 are used as high temperature and low-temperature metal hydrides. One kg of NaMgH2F is used as thermal energy storage media, while Mg2NiH4 is used as hydrogen storage media. The analysis includes the study of energy charging and discharging characteristics with heat transfer phenomenon in metal hydride with variation in thermal conductivity of high temperature metal hydride bed. With the increase in thermal conductivity of high temperature metal hydride bed, the heat transfer between heat transfer fluid and metal hydride bed during the energy charging and discharging process has improved. A marginal increase in thermal energy stored and discharged in/from the metal hydride bed system has been observed with an increase in the thermal conductivity of the metal hydride bed. Thermal energy stored in the MH beds for thermal conductivity of 0.5 W/m K, 0.75 W/m K, and 1 W/mK, are 270.88 kJ, 273.39 kJ, and 274.96 kJ, respectively. The energy desorbed from the system for thermal conductivity 0.5 W/mK, 0.75 W/mK, and 1 W/mK are observed as 251.25 kJ, 258.22 kJ, and 260.57 kJ, respectively. The three cases of thermal conductivity have reported an energy storage efficiency of 92.75%, 94.45%, and 94.77%, respectively.